1987
DOI: 10.1083/jcb.105.1.291
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and the vascular endothelial cytoskeleton.

Abstract: Abstract, Although there is considerable evidence to suggest that hemodynamics play an important role in vascular disease processes, the exact mechanisms are unknown. With this in mind, we have designed a pulsatile perfusion apparatus which reproducibly delivers pulsatile hemodynamics upon freshly excised canine carotid arteries in vitro. Quantifiable simulations included (a) normotension with normal or lowered flow rates (120/80 mmHg, 120 and 40 ml/min), (b) normotension with lowered or elevated transmural pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 24 publications
(34 reference statements)
0
30
1
Order By: Relevance
“…It is widely accepted that actin filaments are responsible for the cells' attachment to the substrate (Franke et al 1984;Herman et al 1987). However, in the present study we observed an accumulation of the intermediate-sized filaments in the cells situated in unfavorable lymphodynamic conditions, with increased shear stress, whereas the stress fibers to which up to now, cell adhesion has been assigned were not detected.…”
Section: Discussioncontrasting
confidence: 53%
“…It is widely accepted that actin filaments are responsible for the cells' attachment to the substrate (Franke et al 1984;Herman et al 1987). However, in the present study we observed an accumulation of the intermediate-sized filaments in the cells situated in unfavorable lymphodynamic conditions, with increased shear stress, whereas the stress fibers to which up to now, cell adhesion has been assigned were not detected.…”
Section: Discussioncontrasting
confidence: 53%
“…The subendothe-Hal structures, however, were not as clearly defined as in the present specimens. Exami nation of published SEMs, however, shows that 1EL fenestra can be seen in other prepa rations with intact endothelium [Herman et al, 1987, fig. 9a], It may be, that these struc tures are more prominent in the present specimens because of the method of fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides family history and genetic factors, there are several mechanical factors that can affect the onset, generation and progression of dissecting aneurysm, including hemodynamics (Herman et al, 1987;Blanco et al, 2006;Feijoo, 2009), vascular geometry (Feijoo, 2009), mechanical properties and composition of the aorta wall (Feijoo, 2009). However, hemodynamics is believed to play a key role in the formation and the progression of the dissecting aneurysm (Herman et al, 1987).…”
Section: Introductionmentioning
confidence: 99%